2017
DOI: 10.1016/j.ydbio.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes are heterogeneous in their origin within the same tissue

Abstract: Pericytes heterogeneity is based on their morphology, distribution, and markers. It is well known that pericytes from different organs may have distinct embryonic sources. Yamazaki et al. (2017) using several transgenic mouse model reveal by cell-lineage tracing that pericytes are even more heterogeneous than previously appreciated. This study shows that pericytes from within the same tissue may be heterogeneous in their origin. Remarkably, a subpopulation of embryonic dermal pericytes derives from the hematop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 137 publications
0
82
0
Order By: Relevance
“…1, 2, 32 For example, brain pericytes have distinct morphologies, markers and functions along the arteriole-capillary-venule vasculature bed. 33 The expression of ACTA2 is weak in the brain pericytes in the middle of capillary bed; however, those in the arteriole-capillary interface express strong ACTA2 and play an important role in blood flow control.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2, 32 For example, brain pericytes have distinct morphologies, markers and functions along the arteriole-capillary-venule vasculature bed. 33 The expression of ACTA2 is weak in the brain pericytes in the middle of capillary bed; however, those in the arteriole-capillary interface express strong ACTA2 and play an important role in blood flow control.…”
Section: Discussionmentioning
confidence: 99%
“…Pericytes are heterogeneous regarding their distribution, phenotype, marker expression, origin, and function [16,3147], several subtypes have been characterized in various organs [11,1720], including the heart [21]. Cardiac pericytes subpopulations, type-1 (NG2 +/Nestin-GFP−) and type-2 (NG2 +/Nestin-GFP +) pericytes, were identified in the perivascular space of cardiac blood vessels using bitransgenic Nestin-GFP/NG2-DsRed mice [21].…”
Section: Perspectives/future Directionsmentioning
confidence: 99%
“…Based on those initial criteria [15], and on the presence of cells that follow these criteria in multiple adult tissues, it was suggested that MSCs have a common origin. Due to the broad organ distribution of blood vessels, the attention had turned to pericytes as candidates to be the MSCs [1618]. Initially, isolation of pericytes followed by long-term culture provided evidence that they acted as stem cells in various tissues [1926].…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%